2008
DOI: 10.1258/jms.2008.007110
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a self-administered decision aid for colorectal cancer screening

Abstract: Unique Protocol ID 211705 ClinicalTrials.gov ID NCT 00148226.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 26 publications
5
99
0
Order By: Relevance
“…This suggests that patient knowledge of their medical condition varies with their general education and socioeconomic status. Although this has not been previously explored in TJA with SDM interventions, our findings are consistent with findings in other fields such as colorectal cancer and breast cancer screening [11,12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that patient knowledge of their medical condition varies with their general education and socioeconomic status. Although this has not been previously explored in TJA with SDM interventions, our findings are consistent with findings in other fields such as colorectal cancer and breast cancer screening [11,12].…”
Section: Discussionsupporting
confidence: 90%
“…However, the impact of DESIs on enhancing decision quality may vary according to education level. For example, the mean increase in knowledge with DESIs may be higher for patients with higher level of education [11]. Alternatively, it may be higher for patients with lower level of education [12], presumably because more educated patients start out with higher baseline scores and subsequently have less room for gain in knowledge.…”
mentioning
confidence: 99%
“…It contained detailed written and numeric information on the outcomes of biennial FOBT over 10 years, tailored by age, gender and family history group. It was evaluated using a randomized trial design, and found to support informed decision making across different education levels [15]. However, it was not specifically designed for, or tested among people with lower literacy.…”
Section: Design Of the Decision Aid (Draft 1)mentioning
confidence: 99%
“…Although some web- and computer-based DAs have focused on prostate [32,42], breast [38], and colorectal cancers [36,43], there have been only a few examples [44] in the literature addressing web- or computer-based DAs to target decisions about cancer clinical trials. The PRE-ACT decision aid was guided by the International Patient Decision Aid Standards (IPDAS) Collaboration [45], which recommends that tools provide: balanced personalized information about options, sufficient information to ensure the patient is knowledgeable about options, facts about outcomes and probabilities, personal values related to options, and guidance in steps of deliberation and communication to match decisions with personal values.…”
Section: Introductionmentioning
confidence: 99%